Influence of Nursing Faculty Discussion Presence on Student Learning and Satisfaction in Online Courses. Issue 4 (July 2016) - Claywell, Lora; Wallace, Cara; Price, Jill; Reneau, Margaret; Carlson, Kathleen
Abstract : This study determined the relationships between faculty participation in online discussions with student satisfaction and perceived learning in online RN-BSN and MSN courses. Analysis of faculty participation in online courses (n = 280) demonstrated a relationship between faculty participation and student satisfaction and perceived learning. The results of this study offer guidance on the minimal faculty participation necessary in online discussions in nursing courses.